Phenotypic and Genotypic Characterization of Enterobacteriaceae Producing Oxacillinase-48–Like Carbapenemases, United States - Joseph D. Lutgring; Wenming Zhu; Tom J.B. de Man; Johannetsy J. Avillan; Karen F. Anderson; David R. Lonsway; Lori A. Rowe; Dhwani Batra; J. Kamile Rasheed; Brandi M. Limbago (Emerging Infectious Diseases, 2018)
Oxacillinase (OXA)–48–like carbapenemases remain relatively uncommon in the United States. We performed phenotypic and genotypic characterization of 30 Enterobacteriaceae producing OXA-48–like carbapenemases that were recovered from patients during 2010–2014. Isolates were collected from 12 states and not associated with outbreaks, although we could not exclude limited local transmission. The alleles β-lactamase OXA-181 (blaOXA-181) (43%), blaOXA-232 (33%), and blaOXA-48 (23%) were found. All isolates were resistant to ertapenem and showed positive results for the ertapenem and meropenem modified Hodge test and the modified carbapenem inactivation method; 73% showed a positive result for the Carba Nordmann–Poirel test. Whole-genome sequencing identified extended-spectrum β-lactamase genes in 93% of isolates. In all blaOXA-232 isolates, the gene was on a ColKP3 plasmid. A total of 12 of 13 isolates harboring blaOXA-181 contained the insertion sequence ΔISEcp1. In all isolates with blaOXA-48, the gene was located on a TN1999 transposon; these isolates also carried IncL/M plasmids.